HELPING TENANTS STAY IN LOW-INCOME SENIOR HOUSING: PREDICTIVE VALIDITY OF THE LIVE WELL AT HOME RAPID SCREEN. (11th November 2018) - Zheng, M; Harding, K; Kane, R
Abstract: The Live Well at Home-Rapid Screen (LWAH-RS) aims to identify older adults' risks for nursing home admission. With only 7 items and a theoretical score from 0 to 12, the LWAH-RS is widely recommended for use in subsidized senior housing. The current study took place in CommonBond Communities (CBC), a housing agency that uses the LWAH-RS to assess its tenants in 26 sites. Using the CBC database, we selected tenants over age 60 who completed the LWAH-RS (n=103). Logistic regression was used to examine if the LWAH-RS can predict whether a tenant continues to live independently or needs a higher level of care, controlling for demographic characteristics (e.g. age, gender, race, income) and environmental support (e.g. living alone or with family, program participation, and the number of times interacting with housing service coordinators). The results from the logistic regression model showed that we improved the prediction of tenants' housing arrangement 3 years after the screening by nearly one-third (30.1%). A one-point increase in the LWAH-RS score was associated with over twice the odds of nursing home admissions, controlling for other factors (OR = 2.12, p < .001). Given that the LWAH-RS is useful in predicting nursing home admission among older adults living in subsidized housing, housing service coordinators can provide the tenants with necessary resources to address the risk factors for nursing home admission based on the LWAH-RS result, such as fall prevention services and in-home services.